PDGF-BB induces intratumoral lymphangiogenesis and promotes lymphatic metastasis. - Cao, R; Björndahl, M; Religa, P; Clasper, S; Garvin, S; Galter, D; Meister, B; Ikomi, F; Tritsaris, K; Dissing, S; Ohhashi, T; Jackson, D; et al. (2004)
Cancer metastases are commonly found in the lymphatic system. Like tumor blood angiogenesis, stimulation of tumor lymphangiogenesis may require the interplay of several tumor-derived growth factors. Here we report that members of the PDGF family act as lymphangiogenic factors. In vitro, PDGF-BB stimulated MAP kinase activity and cell motility of isolated lymphatic endothelial cells. In vivo, PDGF-BB potently induced growth of lymphatic vessels. Expression of PDGF-BB in murine fibrosarcoma cells induced tumor lymphangiogenesis, leading to enhanced metastasis in lymph nodes. These data demonstrate that PDGF-BB is an important growth factor contributing to lymphatic metastasis. Thus, blockage of PDGF-induced lymphangiogenesis may provide a novel approach for prevention and treatment of lymphatic metastasis.